Institute of Public Relations Malaysia: a historical perspective - Syed Abdullah Idid, Syed Arabi (Research Centre, International Islamic University Malaysia, 2005)
The institute of Public Relations Malaysia (IPRM) was established in 1962 to advance the interests of public relations in Malaysia. The development of public relations in Malaysia during the last 40 years must be seen within the context of the nation's metamorphoses as well. This book would suggest to the readers how the developments in the country played a part in shaping public relations and the IPRM itself. This brief history of IPRM is written based on sources, such as minutes of meetings, brochures, correspondences and official newsletters. Some past and current members too had offered to share their own experiences and other information about the Institute. However, it is sad that some data may be lost forever. It has taken the author more than three years to collect and sieve through the available records in order to write this brief history. This book is dedicated in memory of the founding president, the late Dato' Mohd Sopiee Sheikh Ibrahim, who made all things happen.